Retroperitoneal Liposarcoma: Current Insights in Diagnosis and Treatment - Matthyssens, Lucas E.; Creytens, David; Ceelen, Wim P. (Frontiers in Surgery, 2015)
Retroperitoneal liposarcoma (RLS) are rare, biologically heterogeneous tumors that present considerable challenges due to their size and deep location. As a consequence, the majority of patients with high grade RLS will develop locally recurrent disease following surgery, and this constitutes the cause of death in most patients. Here, we review current insights and controversies regarding histology, molecular biology, extent of surgery, (neo)adjuvant treatment, and systemic treatment including novel targeted agents in RLS.